Quagga and zebra mussels : biology, impacts, and control - Nalepa, T. F.; Schloesser, Donald W. (Taylor & Francis, 2014)
"The introduction and rapid spread of the zebra mussel in North American waters has caused great concern among industrial and recreational users of these waters. This bivalve mollusk is a biofouler that attaches to any firm substrate (e.g. rocks, piers, water intake pipes, boat hulls) and has already created significant problems for raw water users such as water treatment plants and power plants. Quagga and Zebra Mussels : Biology, Impacts and Control provides essential information regarding the biology of the zebra mussel in North America and Europe, presents case studies of environmental and industrial impacts, and outlines control strategies. Summary articles detail its life history, origins, and morphology. The book also examines techniques used to culture and maintain this organism in the laboratory. Thirty-two color plates illustrate some of the dramatic problems created by the explosive population growth of this species. Quagga and Zebra Mussels : Biology, Impacts, and Control is an important resource for ecologists, conservationists, environmental consultants, water quality engineers, regulatory officials, power utilities, and libraries"-- Provided by publisher.
"A CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa plc."
Keywords: Zebra mussel.; Quagga mussel.; Zebra mussel -- Control.; Quagga mussel -- Control.; Zebra mussel -- Environmental aspects.; Quagga mussel -- Environmental aspects.; elektronické knihy; electronic books